Adapting the Uppsala model to a modern world: Macro-context and microfoundations. Issue 9 (December 2017) - Coviello, Nicole; Kano, Liena; Liesch, Peter
Abstract Vahlne and Johanson (2017) present the multinational business enterprise (MBE) as a new form of cross-border organization that supersedes the multinational enterprise (MNE). They offer a 'general model of the evolution of the MBE, ' arguing that the MBE evolves through ongoing internationalization processes by proactively and entrepreneurially engaging in business exchange rather than production. In this counterpoint, we focus on two critical dimensions absent from Vahlne and Johanson's (2017) arguments: the impact of the digital context as a defining macro-level feature of our modern world, and the role of the individual as a core microfoundation of the internationalization process. We argue that a robust theory of the evolution of the modern firm must necessarily account for these dimensions. To explicate these impacts, we draw from a range of complementary research streams across international business, entrepreneurship, and international entrepreneurship. We identify research implications for scholars seeking to further advance the Uppsala model of internationalization and those who will use the revised model to study the modern multinational. Résumé Vahlne et Johanson (2017) présentent l'entreprise d'affaires multinationales (EAM) comme une nouvelle forme d'organisation transfrontalière qui remplace l'entreprise multinationale (EMN). Ils offrent un 'modèle général d'évolution de l'EAM, ' avançant que l'EAM évolue par le biais d'un processus continu d'internationalisation en s'engageant de manière proactive et entrepreneuriale dans des échanges d'affaires plutôt que dans des productions. Dans ce contrepoint, nous nous concentrons sur deux dimensions critiques qui sont absentes des arguments de Vahlne et Johanson (2017): l'impact du contexte digital comme un élément définissant le niveau marco-environnemental de notre monde moderne et le rôle de l'individu comme une micro-fondation clé du processus d'internationalisation. Nous avançons qu'une théorie robuste de l'évolution de la firme moderne doit nécessairement prendre en compte ces dimensions. Pour expliquer ses impacts, nous nous appuyons sur une série de courants de recherche complémentaires eninternational business, en entrepreneuriat et en entrepreneuriat international. Nous identifions les implications au niveau de la recherche pour les chercheurs qui visent à développer davantage le modèle d'internationalisation d'Uppsala et ceux qui vont utiliser le modèle revisité pour étudier la multinationale moderne. Resumen Valhne y Johanson (2017) presentan a la empresa de negocios multinacionales (MBE) como una nueva forma de organización transfronteriza que sustituye la empresa multinacional (MNE). Ellos ofrecen un "modelo general de la evolución de la MBE", argumentando que la MBE evoluciona mediante procesos de internacionalización en curso a través de participar de manera emprendedora y proactiva en el intercambio de negocios en lugar de producción. En este contra punto, nos enfocamos en dos dimensiones críticas ausentes en los argumentos de Valhne y Johanson (2017): el impacto del contexto digital como una característica definitoria a nivel macro de nuestro mundo moderno, y en el papel del individuo como una micro-fundación central del proceso de internacionalización. Argumentamos que una teoría robusta de la evolución de la empresa moderna debe necesariamente tener en cuentas estas dimensiones. Para explicar estos impactos, extraemos de una variedad de corrientes de investigación complementarias a través de negocios internacionales, emprendimiento y emprendimiento internacional. Identificamos implicaciones de investigación para los académicos que buscan avanzar el modelo Uppsala de internacionalización y para aquellos que usaran el modelo para estudiar la multinacional moderna. Resumo Vahlne e Johanson (2017) apresentam a empresa multinacional de negócios (MBE) como uma nova forma de organização transfronteiriça que substitui a empresa multinacional (MNE). Eles oferecem um "modelo geral da evolução da MBE", argumentando que a MBE evolui através dos processos de internacionalização em curso, de forma proativa e empreendedora envolvendo-se na troca de negócios, em vez de produção. Neste contraponto, nos concentramos em duas dimensões críticas ausentes nos argumentos de Vahlne e Johanson (2017): o impacto do contexto digital como uma característica macro definidora do nosso mundo moderno e o papel do indivíduo como micro fundamento central do processo de internacionalização. Argumentamos que uma teoria robusta da evolução da empresa moderna deve necessariamente considerar essas dimensões. Para explicar esses impactos, extraímos de uma série de linhas de pesquisa complementares em negócios internacionais, empreendedorismo e empreendedorismo internacional. Identificamos as implicações da pesquisa para acadêmicos que procuram avançar o modelo Uppsala de internacionalização e para aqueles que usarão o modelo revisado para estudar a multinacional moderna. 摘要 Vahlne和Johanson(2017)将跨国商业企业(MBE)作为替代跨国企业(MNE)的跨境组织的一种新形式。他们提出了"MBE进化的通用模型", 认为MBE是通过主动地和具有创业精神地从事商业往来的而不是生产的持续国际化进程进化的。在这篇对论中, 我们关注Vahlne和Johanson(2017)的论点中没有的两个关键维度:作为定义我们现代世界宏观层面特征的数字情境的影响, 以及作为国际化进程核心微观基础的个体的作用。我们认为现代公司进化的扎实的理论必需说明这些维度。为了阐明这些影响, 我们借鉴了一系列跨越国际商务、创业和国际创业的互补的研究流派。我们确定了对寻求进一步改进乌普萨拉国际化模型的学者们以及那些将使用修订后的模型去研究现​​代跨国公司的学者们的研究启示。.